Who, what, and when: A descriptive examination of crowd formation, crowd behavior, and participation with law enforcement at homicide scenes in one city - Lacks, Robyn Diehl (American journal of criminal justice, 2005)
This study provides a descriptive look at the characteristics, behaviors, and differences of crowds and crowd formation that emerge as a result of a homicide. The research was conducted as a result of anecdotal information provided by law enforcement officers who conveyed concern over the “dysfunctional” behaviors and lack of participation with law enforcement occurring at homicide scenes. The theoretical foundation for the study is grounded in the literature surrounding crowd formation and group norms. The study uncovered a variety of factors related to crowd size and participation with law enforcement. Noteworthy is the finding that reveals the classification of the homicide (drug-related or non-drug related) is related to crowd size, participation with law enforcement, and victim characteristics.